Calculation of the magnetic field of the asteroid 4 Vesta parent body (Application of SK theory) - Violeta N Nikolić (Annals of Mathematics and Physics - Peertechz Publications, 2023)
The SK theory provides a deeper insight into the magnetic properties of celestial bodies. In this study, the magnetic field calculated of the parent body of asteroid 4 Vesta, could facilitate deeper insight into the formation of planets or the Universe.